The teaching work in the post graduation program: pleasure and suffering - Bruna Lecintia Carpes Souto; Carmem Lúcia Colomé Beck; Liliane Ribeiro Trindade; Rosângela Marion da Silva; Dirce Stein Backes; Rodrigo Almeida Bastos (Universidade Federal de Santa Maria, 2017)
Aim: to describe the feelings of pleasure and suffering during the postgraduate teaching work from the perspective of the teachers. Method: exploratory descriptive, qualitative study, whose data were collected through a semistructured interview, with six professors of postgraduate programs at the master's degree level of a Federal University. Content analysis was chosen for data analysis. Results: the results showed that the construction of the teaching identity, the visibility and recognition are important factors for the exercise of the profession and that pleasure at work is possible when one does what one likes. Suffering is expressed from everyday elements such as work overload, bureaucracy and frustration, although it is not recognized by the research participants. Final considerations: the dynamic of the feelings of pleasure and suffering indicates that the feelings of pleasure stood out in relation to those of suffering, which suggests signs of denial of the latter.